1974
DOI: 10.1007/bf01956174
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of heavy metals in the red abalone,Haliotis rufescens, on the California coast

Abstract: The gills, mantle, digestive gland and foot muscle of 74 specimens of the red abalone, Haliotis rufescens, from five localities on the California coast were analyzed for eight heavy metals: Ag, Cd, Cr, Cu, Pb, Hg, Ni, and Zn. The distribution of these elements in the abalones appeared to be non-normal and the non-parametric Wilcoxon U statistic was used to compare sample concentrations. No correlation of metal concentration with size was found. High concentrations of Cd (up to 1400 ppm) were found in the diges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1975
1975
1993
1993

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 15 publications
(11 reference statements)
1
9
0
Order By: Relevance
“…This agrees with Marks (1938) who found no effect of size on levels of copper in H.fulgens. Anderlini (1974) was unable to find any relationship for copper or other metals, although this conclusion was based on the analyses of individual tissues in H. rufescens.…”
Section: Effect Of Size On Metal Concentrationsmentioning
confidence: 91%
See 2 more Smart Citations
“…This agrees with Marks (1938) who found no effect of size on levels of copper in H.fulgens. Anderlini (1974) was unable to find any relationship for copper or other metals, although this conclusion was based on the analyses of individual tissues in H. rufescens.…”
Section: Effect Of Size On Metal Concentrationsmentioning
confidence: 91%
“…However, nickel which is concentrated in the mantle and copper which is concentrated in the blood are notable exceptions (see Discussion). Concentrations in the digestive gland of//, tuberculata are compared in Table 2 with values given by Anderlini (1974) for H. rufescens from California. His ranges of mean values from five sites, some of which were contaminated, are given and show that concentrations in H. tuberculata are generally at the low end of the range or lower than those for the American species.…”
Section: Metals In Different Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Standard additions were used to check the recoveries of metals. This enabled corrections to be made for the effect of iron on chromium analyses of sediments and showed that analyses of silver in tissues were not seriously affected by lipids which are difficult to digest with nitric acid (Anderlini, 1974). Thornton, Watling & Darracott (1975) have advocated the analysis of freshwater sediment as a means of recognizing areas of mineralization or metal contamination.…”
Section: E T H O D Smentioning
confidence: 99%
“…In the terrestrial prosobranch Pomatias, concretions in the digestive gland contain iron as well as zinc, and in other species they may be rich in silica and aluminium (Martoja & Martoja, 1973). In Haliotis, the mantle tissue concentrates nickel (Bryan, Potts & Forster, 1977), and it has been suggested by Anderlini (1974) that some adsorption by mucus may be involved in nickel accumulation. The understanding of the mechanisms of uptake, storage and excretion of these heavy metals requires a great deal of further work.…”
Section: Trace Elementsmentioning
confidence: 99%